Simulating the Outer Nebula of SN 1987A. Issue Volume 9:Issue S296(2013) (29th January 2014) - Fitzpatrick, Ben; Morris, Thomas; Podsiadlowski, Philipp
Abstract: As has been shown previously, the triple-ring nebula around SN 1987A can be understood as a direct consequence of the merger of two stars, some 20, 000 yr before the explosion. Here we present new SPH simulations that also include the pre-merger mass loss and show that this may be able to explain other structures observed around SN 1987A, such as Napoleon's hat and various light echoes.